PENGARUH MEDIA SOSIAL TIKTOK TERHADAP HASIL BELAJAR PAI SISWA UPT SDN 12 ARUNGKEKE - Ashar; Roslyn; Ayma (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this study was to determine the influence of tik tok social media on student learning outcomes in Islamic religious education subjects UPT SDN 12 Arungkeke, Jeneponto Regency. This type of research is quantitative survey/expost facto research. Research procedures include conceptual stage, design and planning phase, instrument making and research data collection, empirical phase, analytical phase (analyzing data and calculating research data results), and disimina (designing research results). The results showed that in the T test seen from the value of Tcalculate (89,584) > Ttable (1,713) or a significant probability value of 0.000 < 0.05, Ho was rejected and Ha was accepted, meaning that social media tik tok (X) had a positive and significant effect on student learning outcomes (Y). Based on student learning outcomes and testing that has been carried out by researchers, it can be seen that tik tok social media affects student learning outcomes in educational subjects phase